Evaluation of clinical periodontal conditions in smokers and non-smokers - Luzzi, Lucinara Ignez Tavares [UNESP]; Greghi, Sebastião Luiz Aguiar [UNESP]; Passanezi, Euloir [UNESP]; Sant'Ana, Adriana Campos Passanezi [UNESP]; Lauris, José Roberto Pereira [UNESP]; Cestari, Tânia Mary [UNESP] (FapUNIFESP (SciELO), 2007)
Given that tobacco smoking habit is a risk factor for periodontal diseases, the aim of this study was to compare clinical periodontal aspects between smokers and non-smokers. The clinical status were assessed in 55 patients, 29 smokers and 26 non-smokers, aged 30 to 50 years, with mean age of 40. The clinical parameters used were: probing depth (PD), plaque index (PI), gingival index (GI), clinical attachment level (CAL), gingival recession (GR) and gingival bleeding index (GBI) for arches (upper and lower ) and teeth (anterior and posterior). Tooth loss was also evaluated in both groups. Multiple regression analysis showed: tendency of greater probing depth and clinical attachment level means for smokers; greater amount of plaque in smokers in all regions; greater gingival index means for non-smokers with clinical significance (p<0.05) in all regions. Although, without statistical significance, the analysis showed greater gingival bleeding index means almost always for nonsmokers; similar gingival recession means in both groups and tendency of upper tooth loss in smokers and lower tooth loss in non-smokers. The findings of this study showed that clinical periodontal parameters may be different in smokers when compared to non-smokers and that masking of some periodontal signs can be a result of nicotine's vasoconstrictor effect.
Keywords: Periodontal disease; Periodontal parameters; Smoking